SDSS J100711.74+193056.2: A Candidate Common Motion Substellar Companion to the Nearest B-type Star Regulus - Eric E. Mamajek; Adam J. Burgasser (The Astronomical Journal)
The L9 dwarf SDSS J100711.74+193056.2 is situated 7 $\mathop{.}\limits^{^° }$ 5 north of the nearest B-type star Regulus ( d = 24.3 ± 0.2 pc), part of a stellar quadruplet. The object is at similar distance ( d = 21.9 ± 1.0 pc) as Regulus, with a 3D separation of $3.{9}_{-0.5}^{+0.6}$ pc (~1.6 tidal radii from Regulus), and shares tangential motion within 2 km s ^−1 , hinting at a physical connection. Near-infrared spectroscopy with Keck/NIRES finds that SDSS J100711.74+193056.2 also has a comparable radial velocity as Regulus A and B, a metallicity similar to Regulus B, and a spectral morphology consistent with the estimated 1–2 Gyr total age of Regulus's close pre-white-dwarf companion. Taken together, these observations indicate that SDSS J100711.74+193056.2 is a very widely separated and potentially physically bound companion to Regulus, with a binding energy and mass ratio comparable to other wide star-brown dwarf systems. It joins a growing list of brown dwarfs at the L-dwarf/T-dwarf transition with independent constraints on physical properties such as age and metallicity.